Postpartum preeclampsia following syntometrine injection in uterine atony - Md Mukhtar, Nur Zila; Abd Ghani, Muhamad Rasydan; Xiang Yan, Pok; Ab Rahman, Azrul Shahnazir (Kugler Publications, 2022)
We report a case of a parturient with Diabetes Mellitus complicating pregnancy underwent CS for 2 previous scars. Subarachnoic block and ITM were given. IM Ergometrine was added to Pitocin infusion post-delivery due to the presence of uterine atony. Total operative time was 60 minutes with estimated blood loss of 700mls. She was given bilateral TAP block postoperatively. 25 minutes post-syntometrine, blood pressure increased ranging between 170 to 200/110 to 130 mmHg and she complaint of headache. She was started on Labetolol infusion up to maximum of 80mg/h after not responding to boluses of IV Labetolol and oral Nifedipine. Labetolol infusion was off 9 hours post-Syntrometrine administration and BP was controlled with oral labetolol afterwards. Diagnosis of preeclampsia was established postoperatively based on urine protein-to-creatinine ratio of 97.9 mg/mmol. In terms of pain control, as compared to 2 previous operations done under ITM, current pregnancy has better pain controlled.